Hamlet - Shakespeare, William; Thompson, Ann; Taylor, Neil (New Delhi : Bloomsbury, 2017)
"This Arden edition of Hamlet, arguably Shakespeare's greatest tragedy, presents an authoritative, modernized text based on the second quarto text with a new introductory essay covering key productions and criticism in the decade since its first publication. A timely up-to-date in the 400th anniversary year of Shakespeare's death which will ensure the Arden edition continues to offer students a comprehensive and current critical account of the play, alongside the most reliable and fully-annotated text available."--
Keywords: Shakespeare, William, -- 1564-1616.; Kings and rulers--Succession; Murder victims' families